World Quest: 1: Teacher's Book Pack - Raynham, Alex (Oxford Oxford University Press, 2013)
A teacher$1 (Bs guide for World Quest 1, providing lesson plans, answer keys, and supplementary exercises.s
Vocabulary introduction, lesson plans, additional exercises.
Includes answer keys and teacher's guide.
Keywords: Study and teaching (Elementary)